2001
DOI: 10.1038/oby.2001.16
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid (CLA), Body Fat, and Apoptosis*

Abstract: Obes Res. 2001;9:129 -134. Objective: The objective of the study was to determine if consumption of conjugated linoleic acid (CLA) by mice could induce apoptosis in adipose tissue. Other objectives were to determine the influence of feeding mice CLA for Յ2 weeks on body fat, energy expenditure, and feed intake. Research Methods and Procedures:A mixture of CLA isomers (predominantly c9,t11 and t10,c12) was included in the AIN-93G diet at 0, 1, and 2%, and fed to mice for 12 days (Trial 1), or was included at 2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
1
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 18 publications
(32 reference statements)
7
64
1
10
Order By: Relevance
“…Trans-10,cis-12 CLA reduces lipogenesis in human 37 and mice adipocytes, decreasing sterol regulatory element-binding protein-1 (SREBP-1) expression in vivo 39 . Trans-10,cis-12 CLA also induces adipocyte apoptosis in mice [39][40][41][42][43] , perhaps mediated by an increase in tumour necrosis factor alpha (TNFa) 39 , but the effects of CLA on lipolysis in vivo and in vitro are conflicting 10,38 . Data regarding its effects on preadipocyte differentiation are inconclusive, possibly depending on species, CLA isomer and experimental conditions 4,37 .…”
Section: Effects Of Conjugated Linoleic Acid On Adipocytesmentioning
confidence: 99%
“…Trans-10,cis-12 CLA reduces lipogenesis in human 37 and mice adipocytes, decreasing sterol regulatory element-binding protein-1 (SREBP-1) expression in vivo 39 . Trans-10,cis-12 CLA also induces adipocyte apoptosis in mice [39][40][41][42][43] , perhaps mediated by an increase in tumour necrosis factor alpha (TNFa) 39 , but the effects of CLA on lipolysis in vivo and in vitro are conflicting 10,38 . Data regarding its effects on preadipocyte differentiation are inconclusive, possibly depending on species, CLA isomer and experimental conditions 4,37 .…”
Section: Effects Of Conjugated Linoleic Acid On Adipocytesmentioning
confidence: 99%
“…3,[5][6][7] However, effects on body weight are controversial. Some investigators found reduced body weight after a CLA diet, 4,5,7 whereas others found no effect 3,6,[9][10][11] or an increase in body weight. 11 Furthermore, CLA intake has been associated with an increased energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators found reduced body weight after a CLA diet, 4,5,7 whereas others found no effect 3,6,[9][10][11] or an increase in body weight. 11 Furthermore, CLA intake has been associated with an increased energy expenditure. 4,9,12 Only a few human studies have been conducted to study the effect of CLA on body weight, body mass index (BMI) and/or fat mass.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction that we found in the mRNA expression of these transcriptional factors, induced by trans-10,cis-12, paralleled changes observed in ACC and FAS. Concerning the effects of CLA on liver, several studies in mice have shown that trans-10,cis-12 increased liver weight [8][9][10][11][12][13]. In some of these trials, hepatic triacylglycerol content was measured and it was concluded that hepatomegaly was due to lipid accumulation [5,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%